2020
DOI: 10.3390/nu12103144
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial Testing the Effectiveness of Coping with Cancer in the Kitchen, a Nutrition Education Program for Cancer Survivors

Abstract: Following a diet rich in whole grains, vegetables, fruit, and beans may reduce cancer incidence and mortality. The aim of this study was to investigate the effect of Coping with Cancer in the Kitchen (CCK), an 8 week in-person program offering education, culinary demonstrations and food tasting, and psychosocial group support, compared to receiving CCK printed materials by mail on knowledge, confidence, and skills in implementing a plant-based diet. A total of 54 adult cancer survivors were randomly assigned t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…Gender-related differences. Excepting from the work of Clark-Cutaia et al [38] in which women represent 37% of the studied population with a limited cohort not letting a deep comparison between male and female, in all the other examined studies the majority of the involved population is composed by women (100% in Bernard-Davila et al [39] consisting in breast cancer Hispanic survivors; in Mofleh et al [41], 97.7% of a population of educators from USA; 87% in Mendonça et al [40] from the Health Academy Program in Brazil; 58% in Miller et al [37] consisting in breast cancer survivors). Among women, as a synthetic result of all the analyzed studies, differences in the encountered barriers are especially linked to own's body perception, grade of education, being employed, need to take care of families, and economic concerns.…”
Section: Barriers To a Healthy Dietmentioning
confidence: 89%
See 1 more Smart Citation
“…Gender-related differences. Excepting from the work of Clark-Cutaia et al [38] in which women represent 37% of the studied population with a limited cohort not letting a deep comparison between male and female, in all the other examined studies the majority of the involved population is composed by women (100% in Bernard-Davila et al [39] consisting in breast cancer Hispanic survivors; in Mofleh et al [41], 97.7% of a population of educators from USA; 87% in Mendonça et al [40] from the Health Academy Program in Brazil; 58% in Miller et al [37] consisting in breast cancer survivors). Among women, as a synthetic result of all the analyzed studies, differences in the encountered barriers are especially linked to own's body perception, grade of education, being employed, need to take care of families, and economic concerns.…”
Section: Barriers To a Healthy Dietmentioning
confidence: 89%
“…In her work, Spanish monolingualism is one of the main determinants of lack of enrollment in the protocol together with being unemployed and considering the study cost-consuming. Ethnicity seems to not represent a statistically significant element in terms of adherence to a nutritional intervention with or without in-person counseling in Miller et al [37]. In Mofleh et al [41], being white or not does not represent a statistically significant condition for food insecurity in a population of educators from Pennsylvania.…”
Section: Barriers To a Healthy Dietmentioning
confidence: 90%
“…surgery, chemotherapy, radiotherapy and endocrine treatment) [ 129 ] 1 [ 119 ] EORTC-QLQ-PAN26 Pancreatic cancer EORTC questionnaire module used with the EORTC-QLQ-C30 to assess QoL in patients with pancreatic cancer. Includes 26 items related to disease symptoms, treatment side-effects and emotional issues specific to pancreatic cancer [ 129 ] 1 [ 124 ] FACT-G Cancer Questionnaire designed to measure four domains of HRQOL in cancer patients: Physical, social, emotional, and functional well-being [ 130 ] 2 [ 46 , 131 ] FACT-G7 Cancer The FACT-G7 (Functional Assessment of Cancer Therapy-General 7 item) is a shortened version of the FACT-G questionnaire [ 132 ] 1 [ 133 ] FAACT Anorexia and Cachexia by Cancer QoL questionnaire for both cancer and HIV-infected patients with anorexia/cachexia [ 134 ] 1 [ 135 ] FACT-B Cancer (Breast) Self-report instrument designed to measure QoL in patients with breast cancer. The FACT-B consists of the FACT-General (FACT-G) plus specific concerns related to breast cancer) [ 136 ] 1 [ 131 ] FACT-C Cancer (colorectal) Self-report instrument designed to measure QoL in patients with colorectal cancer.…”
Section: Resultsmentioning
confidence: 99%
“…This is in line with prior studies that have reported improved diet quality in participants following participation in teaching kitchen programs. [9][10][11] Razavi et al reported a significant increase in Mediterranean diet score in families following a 6-week Mediterranean diet-focused, randomized teaching kitchen intervention. 11 Dexter et al reported a significant increase in the number of overweight and obese veterans who reported consumption of fruits, vegetables, fish, whole grains, liquid oils, and trans-fat free products following 5-weeks of a teaching kitchen program.…”
Section: Discussionmentioning
confidence: 99%
“…8 Several studies that have reported improved diet quality in participants following participation in teaching kitchen programs. [9][10][11] However, most previous literature on teaching kitchens measure nutrition-related outcomes through nutrition knowledge, cooking behavior, and eating habit questionnaires. Few have used validated nutritional intake methods to quantify nutrient intake and compare with national dietary recommendations and guidelines.…”
Section: Introductionmentioning
confidence: 99%